2020
DOI: 10.21203/rs.3.rs-32651/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subunits of ARID1 serve as novel biomarkers for the sensitivity to immune checkpoint inhibitors and prognosis of advanced non-small cell lung cancer.

Abstract: Introduction Patients with advanced non-small cell lung cancer (NSCLC) benefit from treatment with immune checkpoint inhibitors (ICIs). Biomarkers such as programmed death-ligand 1 (PD-L1), the tumor mutational burden (TMB) and the mismatch repair (MMR) status are used to predict the prognosis of ICIs therapy. Nevertheless, novel biomarkers need to be further investigated, and a systematic prognostic model is needed for the evaluation of the survival risks of ICIs treatment.Methods A cohort of 240 patients who… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, available data revealed that the role of ARID1A in predicting the efficacy of ICI therapy remains controversial. [41,42] In this study, patients with mutated FGF pathway had numerically longer survival than those with unaltered pathway. Aberrant FGF signaling pathway was reported to be associated with indolent behavior and favorable prognosis in patients with BTCs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, available data revealed that the role of ARID1A in predicting the efficacy of ICI therapy remains controversial. [41,42] In this study, patients with mutated FGF pathway had numerically longer survival than those with unaltered pathway. Aberrant FGF signaling pathway was reported to be associated with indolent behavior and favorable prognosis in patients with BTCs.…”
Section: Discussionmentioning
confidence: 52%
“…Patients with ARID1B mutations had longer PFS and OS, which was consistent with findings by Zhu et al40 In contrast, patients harboring ARID1A mutations seemed to have poorer survival, which is inconclusive because of the small sample size ( n = 4). In addition, available data revealed that the role of ARID1A in predicting the efficacy of ICI therapy remains controversial 41,42. In this study, patients with mutated FGF pathway had numerically longer survival than those with unaltered pathway.…”
Section: Discussionmentioning
confidence: 65%